Case Method in The Problem-Based Learning Model to Increase Student Participation in The Basic Physics Course - Hebat Shidow Falah; Jufrida (Jurnal Penelitian Pendidikan IPA, 2024)
Today's lecture activities require more active learning. However, lecture activities in Basic Physics courses often always focus on the lecturer. This research analyzes the application of the case method in increasing student participation in the Basic Physics I course. This research is a 2 cycle of classroom action research applied to the Basic Physics I course in the 2023/2024 academic year. The research design uses a spiral model by Kemmis and McTaggart. The research results showed that there was an increase in student activity scores in cycle 1 and cycle 2, namely 38.86% (poor category) to 69.14 (fair category).